Incidence and associated factors of posterior capsule opacification formation in pseudophakic patients at Cipto Mangunkusumo Hospital : January - December 2010 - Sita Paramitha Ayuningtyas; Tjahjono D Gondhowiardjo (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Objective: Posterior capsule opacification (PCO) is the most common postoperative consequence of cataract surgery which may cause visual acuity reduction. The incidence of PCO in Indonesia has not been reported yet. The objectives of this study were to evaluate three years cumulative incidence of PCO and factors associated with PCO formation at Cipto Mangunkusumo (CM) Hospital. Methods: This was a retrospective descriptive study to patients with uneventful senile cataract surgery in year of 2010. All related data were retrieved from those medical records in year of 2013, which included patient demographics, type of surgery, time of PCO stated, IOL characteristics (material, optic edge design and diametere. Best corrected visual acuity (BCVA) pre operatively, when PCO was determined and Nd:YAG laser (Neodymium- doped yttrium aluminium garnet) was performed in decimal. Result: A total of 578 eyes (485 patients) was involved in this study. Three years cumulative incidence of the PCO was 8.82% (51 eyes). Phacoemulsification surgery was conducted in 496 (85.8%) eyes. The median time to PCO was being determined was 21 months (range 1 to 34 months) with the mean of BCVA was 0.50Â±0.26. Age, gender, and type of surgery had no related factors to PCO, but higher evidence in using of hydrophilic acrylic IOL (10.7%) was found. After laser Nd:YAG laser was performed, BCVA was improved. Conclusion: Three years cumulative incidence of PCO was 8.82% and there was no defined related factor to PCO reformation, but eye had been using hydrophilic acrylic IOL seem to be higher percentage